Second order noise shaping for data-weighted averaging technique to improve sigma-delta DAC performance - Ali Kerem Nahar; Ansam Subhi Jaddar; Hussain K. Khleaf; Mohmmed Jawad Mortada Mobarek (International Journal of Advances in Applied Sciences, 2021)
In general, the noise shaping responses, a cyclic second-order response is delivered by the method of data weighted averaging (DWA) in which the output of the digital-to-analog converter (DAC) is restricted to one of two states. DWA works efficiently for rather low levels of quantizing; it begins presenting considerable difficulties when internal levels of quantizing are extended further. Though, each added bit of internal quantizing causes an exponentially increasing in power dissipation, complexity, and size of the DWA logic and the DAC. This gives a controlled second-order response accounting for the mismatch of the elements of DAC. The multi-bit DAC is made up of numerous single-bit DACs having values thereof chosen via a digital encoder. This research presents a discussion of the influence of mismatching between unit elements of the delta-sigma DAC. This results in a constrained second-order response accounting for a mismatch of DAC elements. The results of the simulation showed how the effectiveness of the DWA method in reducing band tones. Furthermore, the DWA method has proved its efficiency in solving the mismatching of DAC unit elements. The noise of the mismatching elements is enhanced by 11 dB at 0.01 with the proposed DWA, thereby enhancing the efficiency of the DAC in comparison to the efficiency of the DAC with no use of the circuit of DWA.